Ohodnocení přínosu investice z environmentálního hlediska - Honková Irena (Univerzita Pardubice, 2012)
The aim of this article is to evaluate the investment from an environmental point of view because a trend to look at investment from a non-economic perspective is increasing. The analysed investment is a painting cabin with an efficient filter reducing pollution by 97,9 %. The impact of the painting cabin is calculated from the company itself and also for population of the village where the company operates. Two kinds of method are used: market and non-market evaluations. The market evaluation is based on estimation of saving of pollution fees and the non-market evaluation means a value of air quality for residents. In this work two non-economic evaluation methods are used: Willingness to pay (WTP) and Willingness to accept (WTA). The conclusion deals with the results of these methods and especially with a difference between them and gives a recommendation how to estimate the value and investment from an environmental point of view by using WTA/WTP methods.
Evaluation of the contribution of investment from an environmental point of view
Keywords: cost-benefit analysis; non-market evaluation; contingent valuation method (CVM); willingness to pay (WTP); willingness to accept (WTA)